Inquiry into the extent to which standing orders should permit the Attorney General for Northern Ireland to participate in proceedings of the Assembly. together with the minutes of proceedings, written submissions and the minutes of evidence relating to the report /: together with the minutes of proceedings, written submissions and the minutes of evidence relating to the report. Impartiality of the Office of AGNI, registration of interests and participation of the AGNI in Assembly proceedings in respect of areas other than statutory rules : Part 1, (2015) - Northern Ireland., Assembly., Committee on Procedures,
No abstract available